The rise of domestic outsourcing and the evolution of the German wage structure - Goldschmidt, Deborah; Schmieder, Johannes F. (Bonn, 2015)
"The nature of the relationship between employers and employees has been changing over the last decades, with firms increasingly relying on contractors, temp agencies and franchises rather than hiring employees directly. We investigate the impact of this transformation on the wage structure by following jobs that are moved outside of the boundary of lead employers to contracting firms. For this end we develop a new method for identifying outsourcing of food, cleaning, security and logistics services in administrative data using the universe of social security records in Germany. We document a dramatic growth of domestic outsourcing in Germany since the early 1990s. Event-study analyses show that wages in outsourced jobs fall by approximately 10-15% relative to similar jobs that are not outsourced. We find evidence that the wage losses associated with outsourcing stem from a loss of firm-specific rents, suggesting that labor cost savings are an important reason why firms choose to contract out these services. Finally, we tie the increase in outsourcing activity to broader changes in the German wage structure, in particular showing that outsourcing of cleaning, security and logistics services alone accounts for around 10 percent of the increase in German wage inequality since the 1980s."